The Impact of Oil Price Changes on FTSE/JSE Industry Indices Performance - Zengeni, Eddson; Molele, Mashukudu Hartley (Journal of Reviews on Global Economics, 2020)
The impact of oil price changes on stock market index of the JSE, South Africa, was examined using NARDL model using 2008 -2017 monthly data of aggregated industrial indices. All-Share index was incorporated in the estimation equation to represent market factors. The results indicate that in the short-term, the indices responded asymmetrically to oil price changes whilst in the long-term they responded symmetrically. Oil & Gas, Industrials, Consumers services and Technology indices followed oil price change direction whereas Consumer goods and Financials indices opposed oil price change direction. Healthcare and Telecommunications responded in one direction irrespective oil price change direction.